Sistem Penggajian dan Reward Karyawan di Koperasi Al-Mahbub Taman Sari - Hasanah, Shafaratin Nurul (Al-Khidmah: Jurnal Pengabdian Kepada Masyarakat, 2023)
The payroll and reward system is a payment system for services provided by employees whose salaries are paid monthly. Payroll is very important, because employees are very sensitive to errors in terms of unfair payroll. To maintain high employee morale, the company must pay employee salaries and rewards accurately and on time. This study aims to determine the payroll and reward system at the Al-Mahbub Cooperative. This type of research uses descriptive qualitative research with a case study approach. The data sources in this study are primary and secondary data. Data collection techniques used are observation, interviews and documentation. While in the data management process, data reduction, data presentation and verification are carried out. The data validity test used is the credibility test. The results of the study indicate that (1) the payroll and reward system process at the Al-Mahbub cooperative is good, namely it is carried out accurately and on time. where salary recording is done through an application so that it is easy to record. Direct salary payments through employee accounts in a non-cash manner every month, this can be said to be an effective salary payment method. The payroll system according to Mulyadi consists of the documents used, accounting records used, payroll procedures, and functions used in the payroll system are also good. (2) the payroll and reward system at the Al-Mahbub cooperative is in accordance with existing regulations. Because the payroll system uses the principles of justice and truth. It is said to be fair because it assesses based on employee performance, paying attention to work period, work risks and workload. In addition, salaries are also checked for the accuracy of the calculation. The payroll system in improving employee performance is that it is not only salary that motivates employees to improve their performance, there are still other factors, namely rewards are given at the end of each year for exemplary employees.